The Osteopathic Approach to Treating Depression in Children and Adolescents - Ravi Chinsky, OMS-III; Thomas Chan, DO (Osteopathic Family Physician, 2021)
Evidence confirms that children and adolescents can experience the whole spectrum of mood disorders and suffer from the significant morbidity and mortality associated with them. Effective treatment often relies on physicians developing advanced communication skills with their patients. Enhanced communication will help decipher the etiology of the patient’s depression and, in addition to serotonin-regulating medications, will optimize treatment. Osteopathic medicine offers an effective treatment model through osteopathic manipulative treatment (OMT) because of the inseparability of physical and mental health. Osteopathic medicine takes a holistic view in which somatic, visceral and psychological dysfunction are united. Thus, physicians who incorporate OMT into their practice will help treat psychopathologies, such as depression and its accompanying somatic dysfunctions. This paper discusses the epidemiology of depression, the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) depression criteria, screening algorithms, current treatment protocols, osteopathic considerations to treating depression, and lastly, OMT and its role in treatment.